DAMPAK KEPATUHAN WAJIB PAJAK UMKM DALAM MENINGKATKAN PENERIMAAN PAJAK PADA KPP PRATAMA SEKAYU KABUPATEN MUSI BANYUASIN - Farida Aryani (Jurnal Ilmiah Akuntansi Rahmaniyah, 2021)
This research is a descriptive research with quantitative analysis technique using the calculation and graphic illustration to analyze the effects of tax payers compliance in increasing the revenue of UMKN tax at KPP Pratama Sekayu. The purpose of this research is to know the effects of the tax payers compliance in increasing the revenue of UMKM tax at KPP Pratama Sekayu. Data which is analyzed is the data of UMKM tax payers which is registered and paid the tax as well as the target and realization the revenue of UMKM tax. The result of this research shows that the level of tax payers compliance is in the average 63.92%. The UMKM tax payers compliance in paying the tax can not increase the amount of UMKM tax reception due to the fact that the amount of tax payers increases every year, but the realization amount of tax revenue decreases. This thing happens due to the fact that the tax payers who have the compliance to pay the tax are the tax payers who have relatively small revenue. So, in spite of the fact that the amount the tax payers is big, however the effects for the tax revenue realization is still small due to the fact that the amount of the tax paid is small.